Solitary Freedom in Bradley Cooper’s A Star is Born (2018) - Atinia Hidayah (Metaphor, 2019)
This study proposes the revelation of meaning through signification process in a film entitled ‘A Star is Born’ directed by Bradley Cooper and released in 2018. The research intends to discuss the signification process in creating meaning and representation of freedom and loneliness in two major characters. Signification is a process to find meaning and sign is created by generating the matter from objects, images, or sounds. As a qualitative research, this study is conducted by explaining, deciphering, or making representation in order to gain findings. The findings include major signifiers that signify the signification of freedom such as character’s ability to sing and play instruments; and loneliness such as alcohol addiction.